The effect of mycoses on sowing qualities of Sage seeds (Salvia officinalis L.) in the Non-Chernozem soil zone of the Russian Federation - M. V. Toporishcheva; I. N. Korotkikh; V. M. Andreevskaya; A. M. Lisovoy; U. V. Eremina; E. V. Bondareva (Овощи России, 2024)
Relevance.Medicinal sage is a pharmacopoeial species, a valuable essential oil plant. The method of plantation establishment is predominantly seed-based, and the seed material can retain pathogenic microbiota, so the purpose of the study was to identify mycosis pathogens in the seeds of medicinal sage.Materials and methods. The study was carried out on samples from the biological collection of Salvia officinalis seeds (as part of the Unique Scientific Installation “Biological Collections of the All-Russian Research Institute of Medicinal and Aromatic Plants”). Seeds of the 1st–5th and 9th years of storage were collected from the nurseries of the Experimental Field of the All-Russian Research Institute of Medicinal and Aromatic Plants. Research to identify mycoses of sage seeds was carried out at the All-Russian Research Institute of Phytopathology in the innovative laboratory of microbiology. To study the phytopathogens of Salvia officinalis seeds, the method of artificial nutrient media was used.Results. From the study conducted, the effect of predominant pathogen was established. Fungi of the genus Alternaria, when seeds are stored in conditions with a temperature regime of +20...+22℃, have a negative effect on the sowing quality of seeds. Laboratory germination and germination energy of seeds stored in the cold room (0...+5℃) were affected by yeast, a significant decrease in sowing qualities was observed. When seeds were stored in -18℃, the inhibitory effect of temperature on pathogens was found. The dependence of total pathogen infestation on the conditions and term of seed storage was established. The highest percentage of infestation in seeds stored at room temperature was observed in the first 2 years from the time of collection. The development of pathogenic fungi of Alternaria, Phoma and Rhizopus genus was significantly reduced in seeds stored for 5 to 9 years with temperature conditions of 0...+5℃ and -18℃. Rhizopus, Cladosporium cladosporioides and Clonostachys rosea were found in the sample stored for 38 years in the freezer. The dependence of the set of pathogenic microbiota of seeds on the predecessor in the crop rotation was established. The plots from which seeds were collected, except for the sample from the Crimean zonal experimental station of VILR, have different predecessors. The seeds from the first plot showed the highest percentage of fungal infestation with similar pathogen composition. Total infestation and pathogen composition decreased in the second plot. The sample from the third plot was stored for 5 years in the freezer and no seed mycoses were detected in it.